The role of carboplatin in the neoadjuvant chemotherapy treatment of triple negative breast cancer - Aurelio Bartolome Castrellon; Ihor Pidhorecky; Vicente Valero; Luis Estuardo Raez (Frontiers Media S.A., 2017)
Triple negative breast (TNBC) cancer constitutes a heterogeneous group of disease with histologic and molecular differences. Complete pathologic response to neoadjuvant chemotherapy (NACT) in TNBC is associated with improved outcomes. Efforts have been made in identifying drug combinations that will increase the response rate to preoperative chemotherapy. In this review we present recent studies that have incorporated carboplatin (Cb) in the NACT of TNBC. We discuss the homologous recombination deficiency score and the somatic or germline mutation for BRCA as potential biomarkers for future selection of patients that could benefit from the addition of Cb to NACT.